Impact of Plant Growth Promoting Rhizobacteria (PGPR) on Nitrogen Uptake and Yield of Palu Local Shallots - Lisa Indriani Bangkele; Sri Sudewi; Idris; Ratnawati; Arfan (Postgraduate, University of Mataram, 2026)
Plant Growth-Promoting Rhizobacteria (PGPR) play an important role in improving soil microbial populations and enhancing plant growth and nutrient uptake. This study aimed to evaluate the effect of different PGPR concentrations on bacterial colony populations, growth performance, biomass production, and nitrogen uptake of Palu Valley shallot plants. The experiment consisted of four treatments: control (F0), PGPR 10 mL (F1), PGPR 15 mL (F2), and PGPR 20 mL (F3). The observed variables included bacterial colony population, number of shallot bulbs, fresh biomass, dry biomass, and nitrogen uptake. The results showed that PGPR application increased the bacterial colony population in soil, with the highest population recorded in treatment F3 (3.90 × 10⁶ CFU g⁻¹ soil). The average number of shallot bulbs increased from 9 bulbs plant⁻¹ in the control to 12 bulbs plant⁻¹ in treatments F2 and F3. Fresh biomass and dry biomass also increased with higher PGPR concentrations, reaching 11.95 g and 2.42 g respectively in F3. Nitrogen uptake showed a gradual increase from 1.61% in the control to 1.69% in F3. These findings indicate that PGPR application improves soil microbial populations, plant growth, biomass accumulation, and nitrogen uptake in Palu Valley shallot plants, with the 20 mL PGPR (F3) treatment providing the most effective results.